Pengaruh Kinerja Pegawai terhadap Kepuasan Masyarakat di Nagari Simalanggang Kecamatan Payakumbuh Kabupaten Lima Puluh Kota - Putri Maharani, Friska; Lanin, Dasman (Policy, Law and Political Research Center, 2024)
The background to this research arises from the awareness that there are some people who feel dissatisfied with the performance of employees in Nagari Siamalanggang. So this research aims to determine the effect of employee performance on community satisfaction in Nagari Simalanggang. In this study, researchers applied quantitative research methods. Quantitative data was collected using a Likert scale questionnaire which had been tested for validity and reliability. The data analysis technique used in this research uses descriptive analysis techniques. This research was conducted in Nagari Simalanggang, Payakumbuh District, Limapuluh Kota Regency with a total of 317 respondents. Based on the research results, it shows that the influence of employee performance on community satisfaction is 60.7%, while the remaining 39.3% is influenced by other factors outside the variables. Then, the significance level is at the value 0.000, which is if the Sig. = 0.000 which means the significant value < significant criteria (0.05). So it can be said that employee performance has a significant influence on community satisfaction. Overall, the employee performance variable has a Respondent Achievement Rate (TCR) of 75.24%, which is in the good category. Then the overall community satisfaction variable obtained by the Respondent Achievement Level (TCR) was 75.53%, which is in the good category.